Observations of Diurnal to Weekly Variations of Monoterpene-Dominated Fluxes of Volatile Organic Compounds from Mediterranean Forests: Implications for Regional Modeling - Fares, Silvano; Schnitzhofer, Ralf; Jiang, Xiaoyan; Guenther, Alex; Hansel, Armin; Loreto, Francesco (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2013)
The Estate of Castelporziano (Rome, Italy) hosts many ecosystems representative of Mediterranean vegetation, especially holm oak and pine forests and dune vegetation. In this work, basal emission factors (BEFs) of biogenic volatile organic compounds (BVOCs) obtained by Eddy Covariance in a field campaign using a proton transfer reaction-time-of-flight-mass spectrometer (PTR-TOF-MS) were compared to BEFs reported in previous studies that could not measure fluxes in real-time. Globally, broadleaf forests are dominated by isoprene emissions, but these Mediterranean ecosystems are dominated by strong monoterpene emitters, as shown by the new BEFs. The original and new BEFs were used to parametrize the model of emissions of gases and aerosols from nature (MEGAN v2.1), and model outputs were compared with measured fluxes. Results showed good agreement between modeled and measured fluxes when a model was used to predict radiative transfer and energy balance across the canopy. We then evaluated whether changes in BVOC emissions can affect the chemistry of the atmosphere and climate at a regional level. MEGAN was run together with the land surface model (community land model, CLM v4.0) of the community earth system model (CESM v1.0). Results highlighted that tropospheric ozone concentration and air temperature predicted from the model are sensitive to the magnitude of BVOC emissions, thus demonstrating the importance of adopting the proper BEF values for model parametrization.
The following values have no corresponding Zotero field: pub-location: 1155 16TH ST, NW, WASHINGTON, DC 20036 USA publisher: AMER CHEMICAL SOC
Keywords: Emissions; GLOBAL-MODEL; Ozone; PROTON-TRANSFER REACTION; PTR-TOF; QUERCUS-ILEX; REACTION MASS-SPECTROMETRY

In Situ Investigation of Leaf Water Status by Portable Unilateral Nuclear Magnetic Resonance - Capitani, Donatella; Brilli, Federico; Mannina, Luisa; Proietti, Noemi; Loreto, Francesco (PLANT PHYSIOLOGY, 2009)
A portable unilateral nuclear magnetic resonance (NMR) instrument was used to detect in field conditions the water status of leaves of herbaceous crops (Zea mays, Phaseolus vulgaris), mesophyllous trees (Populus nigra), and natural Mediterranean vegetation characterized by water-spending shrubs (Cistus incanus) and water-saving sclerophyllous trees (Quercus ilex). A good relationship was observed between NMR signal, leaf relative water content, and leaf transpiration in herbaceous leaves undergoing fast dehydration or slowly developing a drought stress. A relationship was also observed between NMR signal and water potential of Populus leaves during the development of a water stress and when leaves recovered from the stress. In the natural vegetation, the relationship between NMR signal and water status was found in Cistus, the species characterized by high transpiration rates, when measured during a drought stress period and after a rainfall. In the case of the sclerophyllous Quercus, the NMR signal, the relative water content, and the transpiration rate did not change at different leaf water status, possibly because a large amount of water is compartmentalized in cellular structures and macromolecules. The good association between NMR signal and relative water content was lost in leaves exposed for 24 h to dehydration or to an osmotic stress caused by polyethylene glycol feeding. At this time, the transverse relaxation time became longer than in leaves maintained under optimal water conditions, and two indicators of membrane damage, the ion leakage and the emission of products of membrane lipoxygenation \{[\}(Z)-3-hexenal, (Z)-3-hexenol, and (E)-2-hexenol], increased. These results taken all together give information on the physiological state of a leaf under a developing stress and show the usefulness of the NMR instrumentation for screening vegetation health and fitness in natural and cultivated conditions. It is concluded that the portable unilateral NMR instrument may be usefully employed in field conditions to monitor nondestructively the water status of plants and to assist agricultural practices, such as irrigation scheduling, to minimize stomatal closure and the consequent limitation to plant production.
Keywords: Drought stress; Mediterranean vegetation; natural vegetation; nuclear magnetic resonance; Quercus ilex

In Situ Investigation of Leaf Water Status by Portable Unilateral Nuclear Magnetic Resonance - Capitani, Donatella; Brilli, Federico; Mannina, Luisa; Proietti, Noemi; Loreto, Francesco (PLANT PHYSIOLOGY, 2009)
A portable unilateral nuclear magnetic resonance (NMR) instrument was used to detect in field conditions the water status of leaves of herbaceous crops (Zea mays, Phaseolus vulgaris), mesophyllous trees (Populus nigra), and natural Mediterranean vegetation characterized by water-spending shrubs (Cistus incanus) and water-saving sclerophyllous trees (Quercus ilex). A good relationship was observed between NMR signal, leaf relative water content, and leaf transpiration in herbaceous leaves undergoing fast dehydration or slowly developing a drought stress. A relationship was also observed between NMR signal and water potential of Populus leaves during the development of a water stress and when leaves recovered from the stress. In the natural vegetation, the relationship between NMR signal and water status was found in Cistus, the species characterized by high transpiration rates, when measured during a drought stress period and after a rainfall. In the case of the sclerophyllous Quercus, the NMR signal, the relative water content, and the transpiration rate did not change at different leaf water status, possibly because a large amount of water is compartmentalized in cellular structures and macromolecules. The good association between NMR signal and relative water content was lost in leaves exposed for 24 h to dehydration or to an osmotic stress caused by polyethylene glycol feeding. At this time, the transverse relaxation time became longer than in leaves maintained under optimal water conditions, and two indicators of membrane damage, the ion leakage and the emission of products of membrane lipoxygenation \{[\}(Z)-3-hexenal, (Z)-3-hexenol, and (E)-2-hexenol], increased. These results taken all together give information on the physiological state of a leaf under a developing stress and show the usefulness of the NMR instrumentation for screening vegetation health and fitness in natural and cultivated conditions. It is concluded that the portable unilateral NMR instrument may be usefully employed in field conditions to monitor nondestructively the water status of plants and to assist agricultural practices, such as irrigation scheduling, to minimize stomatal closure and the consequent limitation to plant production.
The following values have no corresponding Zotero field: pub-location: 15501 MONONA DRIVE, ROCKVILLE, MD 20855 USA publisher: AMER SOC PLANT BIOLOGISTS
Keywords: Drought stress; Mediterranean vegetation; natural vegetation; nuclear magnetic resonance; Quercus ilex

The influence of leaf water content and isoprenoids on flammability of some Mediterranean woody species - De Lillis, Manuela; Bianco, Pietro Massimiliano; Loreto, Francesco (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2009)
The impact of water content and isoprenoids on leaf flammability was studied. Field and laboratory experiments were carried out on monoterpene-emitting evergreen broad-leaved species (Quercus ilex, Quercus suber); a needle-leaved species (Pinus halepensis) that emits and stores monoterpenes; an evergreen species (Myrtus communis) that emits isoprene but stores monoterpenes; and a deciduous species (Quercus pubescens) that emits isoprene. Photosynthesis, leaf water content (LWC) and isoprenoid emission were measured. Isoprenoid content was calculated. Temperatures of visible smoke, incandescence and flame appearance were recorded. The LWC significantly correlated with both photosynthesis and isoprenoid emissions. Linear correlation and factorial analysis revealed a positive correlation between temperature of flame appearance and LWC and a negative relationship between temperature of flame appearance and isoprenoid emission. Multiple regression analysis indicated that the temperature of flame appearance was reduced in broadleaved monoterpene-emitting species. In monoterpene emitters, the temperature of flame appearance depended for similar to 65% on LWC, whereas monoterpene emissions explained similar to 35% of the dependency. P. halepensis and M. communis, storing high levels of isoprenoids, ignited at high humidity. The results may be explained if isoprenoids indeed facilitate leaf ignition but, being dissolved in water, isoprenoids are also an indicator of a high water content that decreases flammability.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: CSIRO PUBLISHING
Keywords: fire; flammability phases; Monoterpenes; photosynthesis

Volatile organic compounds from Italian vegetation and their interaction with ozone. - Calfapietra, Carlo; Fares, Silvano; Loreto, Francesco (Environmental pollution (Barking, Essex : 1987), 2009)
Volatile Organic Compounds (VOCs) emitted from vegetation (particularly isoprenoids) represent an important source of atmospheric hydrocarbons almost double the anthropogenic source. When biogenic VOC mix with NO(x) in the presence of UV radiation, ozone (O(3)) is formed. In Italy, optimal conditions for O(3) formation in terms of VOC/NO(x) ratios and abundance of UV radiation occur for long periods of the year. Moreover, Italian vegetation includes several species that are strong and evergreen isoprenoid emitters, and high temperatures for part of the year further stimulate these temperature-dependent emissions. We review emission of isoprenoids from Italian vegetation, current knowledge on the impact of rising O(3) levels on isoprenoid emission, and evidence showing that isoprenoids can increase both the O(3) flux to the plant and protection against oxidative stress because of their antioxidant functions. This trait not only influences plant tolerance to O(3) but also may substantially alter the flux of O(3) between atmosphere and biosphere.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 19019511
Keywords: antioxidant; isoprene; Monoterpene; Ozone flux; VOC

Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions - Vitale, Marcello; Salvatori, Elisabetta; Loreto, Francesco; Fares, Silvano; Manes, Fausto (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.
Keywords: Gas exchange; Holm oak (Quercus ilex); lipoxygenase products; monoterpene emission; o3 flux; photosynthesis; Stomatal conductance

Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions - Vitale, Marcello; Salvatori, Elisabetta; Loreto, Francesco; Fares, Silvano; Manes, Fausto (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.
Keywords: Gas exchange; Holm oak (Quercus ilex); lipoxygenase products; monoterpene emission; o3 flux; photosynthesis; Stomatal conductance

12CO2 emission from different metabolic pathways measured in illuminated and darkened C3 and C4 leaves at low, atmospheric and elevated CO2 concentration - Pinelli, Paola; Loreto, Francesco (Journal of Experimental Botany, 2003)
The detection of 12CO2 emission from leaves in air containing 13CO2 allows simple and fast determination of the CO2 emitted by different sources, which are separated on the basis of their labelling velocity. This technique was exploited to investigate the controversial effect of CO2 concentration on mitochondrial respiration. The 12CO2 emission was measured in illuminated and darkened leaves of one C4 plant and three C3 plants maintained at low (30–50 ppm), atmospheric (350–400 ppm) and elevated (700–800 ppm) CO2 concentration. In C3 leaves, the 12CO2 emission in the light (Rd) was low at ambient CO2 and was further quenched in elevated CO2, when it was often only 20–30% of the 12CO2 emission in the dark, interpreted as the mitochondrial respiration in the dark (Rn). Rn was also reduced in elevated CO2. At low CO2, Rd was often 70–80% of Rn, and a burst of 12CO2 was observed on darkening leaves of Mentha sativa and Phragmites australis after exposure for 4 min to 13CO2 in the light. The burst was partially removed at low oxygen and was never observed in C4 leaves, suggesting that it may be caused by incomplete labelling of the photorespiratory pool at low CO2. This pool may be low in sclerophyllous leaves, as in Quercus ilex where no burst was observed. Rd was inversely associated with photosynthesis, suggesting that the Rd/Rn ratio reflects the refixation of respiratory CO2 by photosynthesizing leaves rather than the inhibition of mitochondrial respiration in the light, and that CO2 produced by mitochondrial respiration in the light is mostly emitted at low CO2, and mostly refixed at elevated CO2.. In the leaves of the C4 species Zea mays, the 12CO2 emission in the light also remained low at low CO2, suggesting efficient CO2 refixation associated with sustained photosynthesis in non‐photorespiratory conditions. However, Rn was inhibited in CO2‐free air, and the velocity of 12CO2 emission after darkening was inversely associated with the CO2 concentration. The emission may be modulated by the presence of post‐illumination CO2 uptake deriving from temporary imbalance between C3 and C4 metabolism. These experiments suggest that this uptake lasts longer at low CO2 and that the imbalance is persistent once it has been generated by exposure to low CO2.
10.1093/jxb/erg187
Keywords: 13C labelling; C3 versus C4 metabolism; mitochondrial respiration; photorespiration; photosynthesis

Fumigation with exogenous monoterpenes of a non-isoprenoid-emitting oak (Quercus suber): monoterpene acquisition, translocation, and effect on the photosynthetic properties at high temperatures - Delfine, Sebastiano; Csiky, Olav; Seufert, Guenther; Loreto, Francesco (New Phytologist, 2000)
We tested if fumigation with exogenous monoterpenes might induce thermotolerance in leaves of an oak species (Quercus suber) which does not form and emit isoprenoids. To understand if exogenous monoterpene fumigation results in internal accumulation of monoterpenes, a physical method of monoterpene extraction was used. The internal content of monoterpenes increased in concert with increasing fumigation doses. This unambiguously demonstrated acquisition of exogenous monoterpenes. We exposed fumigated Q. suber leaves to two cycles of increasing temperatures from 35 to 55°C at 5°C steps. When leaves were exposed to a low dose of exogenous monoterpenes, yielding an internal content similar to that endogenously formed in the leaves of the monoterpene- emitter Q. ilex, no clear improvement in thermotolerance was found. When leaves were exposed to a high dose of exogenous monoterpenes, yielding an internal content of about ®ve fold the endogenous pool of Q. ilex, but comparable with the expected content following stress-induced stomatal closure, photosynthesis inhibition at high temperatures was attenuated. This eﬀect was observed only at temperatures !45°C during the ®rst cycle, but at all temperatures between 35 and 55°C when plants were exposed to two cycles of high temperatures. Monoterpenes were still found in the leaves of Q. suber 12 h after ending the fumigation. Monoterpenes were also found in non-fumigated leaves distant up to 45 cm from the fumigated leaves. If monoterpenes make the photosynthetic apparatus more resistant to high temperatures, the eﬀect might not be limited to the fumigated leaves and might be persistent after fumigation.
Keywords: isoprenoid emission; Monoterpenes; photosynthesis; Quercus suber; thermotolerance

Fumigation with exogenous monoterpenes of a non-isoprenoid-emitting oak (Quercus suber): monoterpene acquisition, translocation, and effect on the photosynthetic properties at high temperatures - Delfine, Sebastiano; Csiky, Olav; Seufert, Guenther; Loreto, Francesco (New Phytologist, 2000)
We tested if fumigation with exogenous monoterpenes might induce thermotolerance in leaves of an oak species (Quercus suber) which does not form and emit isoprenoids. To understand if exogenous monoterpene fumigation results in internal accumulation of monoterpenes, a physical method of monoterpene extraction was used. The internal content of monoterpenes increased in concert with increasing fumigation doses. This unambiguously demonstrated acquisition of exogenous monoterpenes. We exposed fumigated Q. suber leaves to two cycles of increasing temperatures from 35 to 55°C at 5°C steps. When leaves were exposed to a low dose of exogenous monoterpenes, yielding an internal content similar to that endogenously formed in the leaves of the monoterpene- emitter Q. ilex, no clear improvement in thermotolerance was found. When leaves were exposed to a high dose of exogenous monoterpenes, yielding an internal content of about ®ve fold the endogenous pool of Q. ilex, but comparable with the expected content following stress-induced stomatal closure, photosynthesis inhibition at high temperatures was attenuated. This eﬀect was observed only at temperatures !45°C during the ®rst cycle, but at all temperatures between 35 and 55°C when plants were exposed to two cycles of high temperatures. Monoterpenes were still found in the leaves of Q. suber 12 h after ending the fumigation. Monoterpenes were also found in non-fumigated leaves distant up to 45 cm from the fumigated leaves. If monoterpenes make the photosynthetic apparatus more resistant to high temperatures, the eﬀect might not be limited to the fumigated leaves and might be persistent after fumigation.
Keywords: isoprenoid emission; Monoterpenes; photosynthesis; Quercus suber; thermotolerance

A hypothesis on the evolution of isoprenoid emission by oaks based on the correlation between emission type and Quercus taxonomy - Loreto, Francesco; Ciccioli, Paolo; Brancaleoni, Enzo; Valentini, Riccardo; De Lillis, Manuela; Csiky, Olav; Seufert, Guenther (Oecologia, 1998)
We show that Mediterranean oaks that emit isoprene, monoterpenes or no isoprenoids belong to dierent subgenera as indicated by morpho-taxonomy and molecular genetics. On the other hand, oaks from North America and Asia that are taxonomically similar to the Mediterranean monoterpene emitter Q. ilex emit isoprene only. We surmise that isoprene emission is a genetic character which evolved ancestrally in the oak genus since this is the prevalent emission type in oaks widespread around the world and adapted to dierent environments. This ancestral character may have been either lost or modi®ed in more recent clades such as those originating the Mediterranean oaks. If our hy- pothesis is correct then the taxonomy of European oaks is validated by this independent trait. Isoprenoid emis- sion could serve as a chemo-taxonomical marker and could be used to reconstruct the phylogeny of oaks in association with molecular markers.
Keywords: chemo-taxonomy; Evolution; isoprenoid emission; Quercus

Measurement of isoprenoid content in leaves of Mediterranean Quercus spp. by a novel and sensitive method and estimation of the isoprenoid partition between liquid and gas phase inside the leaves - Loreto, Francesco; Ciccioli, Paolo; Brancaleoni, Enzo; Cecinato, Angelo; Frattoni, Massimiliano (Plant Science, 1998)
We used a novel. simple and sensitive method to extract isoprenoids contained in the leaves and compared emission and content of isoprenoids in the leaves of three Mediterranean oak species emitting isoprene (Quercus puhcsccws), monoterpenes (Querc~s ilrs) or non-emitting isoprenoids (Quercus cerris). The content is qualitatively consistent with the emission of isoprenoids by Qucrczls spp. However. the fraction of isoprenoids in the gas phase was estimated to be r 0.02 and 5% of the total content for monoterpenes and isoprene, respectively. On the other hand, the content of monoterpenes in the leaf was much higher than that of isoprene and particularly rich of compounds which can hardly be detected in an emission such as linalool. It is concluded that isoprenoids are contained in temporary pools and that the different partition between gas and liquid phases plays an important role in determining the pool size in isoprene and monoterpene-emitting oaks. The pools of isoprenoid-emitting oaks sustain the emission for few minutes when isoprenoid formation is prevented. which rules out the presence of specialized organs for isoprenoid storage and are absent altogether in non-emitting species.
Keywords: Isoprene emission (content); Monoterpene emission (content): Quercus spp.

Use of the isoprene algorithm for predicting the monoterpene emission from the Mediterranean holm oak Quercus ilex L.: Performance and limits of this approach - Ciccioli, Paolo; Fabozzi, Concetta; Brancaleoni, Enzo; Cecinato, Angelo; Frattoni, Massimiliano; Loreto, Francesco; Kesselmeier, Jürgen; Schäfer, Luise; Bode, Kirsten; Torres, Liberto; Fugit, Jean-Luc (Journal of Geophysical Research: Atmospheres, 1997)
The algorithm developed by Guenther et al. [1991] to describe the organic emission of isoprene-emitting plants has been used for predicting monoterpene emission from Quercus ilex L., an evergreen oak typical of the Mediterranean basin. The dependence of monoterpene emission on photosynthetically active radiation and temperature has been verified through laboratory experiments carried out on single leaves as well as through field measurements at branch level. While the algorithm describes well monoterpene emission under stationary state conditions, it is less accurate when rapid fluctuations of light and temperature take place. Because of this, the isoprene algorithm is capable of predicting the response of Quercus ilex L. with an accuracy better than ±25% only in 65% of the environmental situations experienced by the plant. Field and laboratory observations consistently indicate that temperature oscillations can be an important source for the discrepancies between predicted and observed values as they can generate bursts of emission with values twice as high as those predicted by the algorithm. Possible causes generating these effects are analyzed and critically discussed. In spite of the observed limitations, the isoprene algorithm can successfully describe the biogenic emission from Quercus ilex L., and its use is advantageous as it greatly simplifies regional and global emission models, especially if the light dependence of monoterpene emission is proven to be a widespread phenomenon.
Keywords: Biogenic emission; isoprene algorithm; monoterpene (voyant); Quercus ilex; Temperature

Use of the isoprene algorithm for predicting the monoterpene emission from the Mediterranean holm oak Quercus ilex L.: Performance and limits of this approach - Ciccioli, Paolo; Fabozzi, Concetta; Brancaleoni, Enzo; Cecinato, Angelo; Frattoni, Massimiliano; Loreto, Francesco; Kesselmeier, Jürgen; Schäfer, Luise; Bode, Kirsten; Torres, Liberto; Fugit, Jean-Luc (Journal of Geophysical Research: Atmospheres, 1997)
The algorithm developed by Guenther et al. [1991] to describe the organic emission of isoprene-emitting plants has been used for predicting monoterpene emission from Quercus ilex L., an evergreen oak typical of the Mediterranean basin. The dependence of monoterpene emission on photosynthetically active radiation and temperature has been verified through laboratory experiments carried out on single leaves as well as through field measurements at branch level. While the algorithm describes well monoterpene emission under stationary state conditions, it is less accurate when rapid fluctuations of light and temperature take place. Because of this, the isoprene algorithm is capable of predicting the response of Quercus ilex L. with an accuracy better than ±25% only in 65% of the environmental situations experienced by the plant. Field and laboratory observations consistently indicate that temperature oscillations can be an important source for the discrepancies between predicted and observed values as they can generate bursts of emission with values twice as high as those predicted by the algorithm. Possible causes generating these effects are analyzed and critically discussed. In spite of the observed limitations, the isoprene algorithm can successfully describe the biogenic emission from Quercus ilex L., and its use is advantageous as it greatly simplifies regional and global emission models, especially if the light dependence of monoterpene emission is proven to be a widespread phenomenon.
Keywords: Biogenic emission; isoprene algorithm; monoterpene (voyant); Quercus ilex; Temperature